2006
DOI: 10.1111/j.1468-2397.2006.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating social work: Philippine social work and human rights under martial law

Abstract: This article examines Philippine social work under martial law. The article begins with an account of the assault on human rights under the Marcos regime. It then outlines the response of the mainstream professional community to the challenges under martial law and the implications for contemporary social work practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…The theme of collective blaming reflects the legitimisation of the dominant discourse of the governing party, which in turn raises concerns about the possible ideological alignment of part of SKLEs leadership with the governing regime. This suggestion seems to be similar to the one offered by Yu (2006Yu ( , 2008, Mazibuko & Gray (2004) and Ioakimidis (2011) as to the ideological alignment of the PASWs with the governing regime as a factor that explains their inability to engage in struggles of resistance to oppressive regimes. An additional factor that might explain that inability relates to current pressures and organisational limitations that have resulted in SKLE's casework orientation.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The theme of collective blaming reflects the legitimisation of the dominant discourse of the governing party, which in turn raises concerns about the possible ideological alignment of part of SKLEs leadership with the governing regime. This suggestion seems to be similar to the one offered by Yu (2006Yu ( , 2008, Mazibuko & Gray (2004) and Ioakimidis (2011) as to the ideological alignment of the PASWs with the governing regime as a factor that explains their inability to engage in struggles of resistance to oppressive regimes. An additional factor that might explain that inability relates to current pressures and organisational limitations that have resulted in SKLE's casework orientation.…”
Section: Discussionsupporting
confidence: 76%
“…The inability of PASWs to fulfil their value-based commitment to social justice has been also documented by Yu (2006Yu ( , 2008, Mazibuko and Gray (2004) and Ioakimidis (2011) who explored PASWs' past performance in non-liberal democracies, such as martial law and apartheid. Yu (2006Yu ( , 2008, for example, explored the record of the Philippine PASW under martial rule through a content analysis of the association's journal. He found that the representatives of the profession not only accommodated and failed to challenge the regime, but also legitimised it.…”
Section: Introduction and Contextmentioning
confidence: 93%
See 1 more Smart Citation
“…The record of the professional community under martial law would, however, bear Lutes out. As evidenced by the contents of the professional journal, mainstream Philippine social work failed to critically position itself against the Marcos dictatorship, contributing instead to its legitimation (Yu, 2006).…”
Section: Implications For Contemporary Practicementioning
confidence: 99%
“…Earlier assumptions that professional progress was part of the 'natural order' have been challenged by policies that reflect, at best, an ambivalent view of social work (Dominelli, 1996;Gray & Mazibuko, 2002). On the other hand, there are indications that social work is rapidly emerging in several countries in which it had either been suppressed altogether or coopted by repressive governments (Iarskaia-Smirnova & Romanov, 2002;Yu, 2006;Yuen-Tsang & Wang, 2002).…”
Section: Introductionmentioning
confidence: 99%